(untitled) (Международный научный журнал «Инженер», 2026)
This article discusses the consequences of the depletion of drinking water, one of the urgent problems of today, and solutions to the problem, improving water quality through filtration, the productive use of local Kyzylkum sand as a method of reuse, the difference between Kyzylkum sand and other local raw materials, the effectiveness of water filtered through Kyzylkum sand (especially black sand), the issue of wastewater and technical water purification and recycling from this sand. An experiment was conducted based on Darcy’s law and a device was built based on this law. The work being done in developed countries in this regard, their significance, and practical application were discussed. The results of the analyzes and experiments conducted using the V1100 spectrophotometer and TDS&EC testers are presented in the form of tables, figures, and diagrams.